A Conceptual Approach to Patient-Physician Relationship - (:unkn) unknown (My University, 2021)
The quality of the patient-physician relationship affects the patient's compliance with the treatment and satisfaction with theinterview. Szasz and Hollender (1956) described three types of patient-physician relationships. In the relationship based onactivity-passivity, the physician is equipped with broad powers, regardless of the patient's consent. Relationship based onguidance-cooperation defines the relationship between the patient who is ready to apply the commands of the physician andthe physician who offers his professional experience. Relationship based on mutual participation is the patient-physicianrelationship when the physician provides professional support for the individual to contribute to his or her health. Patientphysician relationship was modeled by Emanuel EJ and Emanuel LL (1992) with a four-component classification. Thephysician who adopts authoritarian attitude in the paternalistic model can ignore his patient's preferences. In the informativemodel, all the information about the situation is presented to the patient, the patient makes his own choice and the physicianapplies the selected medical intervention. In the interpretive model, the physician sets out the patient's expectation, while doingso, takes the patient's values as reference and shapes the treatment on this basis. In the deliberative model that encouragesshared decision-making between the physician and the patient, the physician and the patient discuss mutually about whatoptions the patient can choose during the treatment process and the path to be followed. It should not be forgotten that the typeof relationship to be adopted in the clinical interview may vary depending on the condition of the patient and the nature of thedisease.

Hasta-hekim ilişkisinin niteliği, hastanın tedaviye gösterdiği uyumu ve görüşmeden memnuniyetini etkilemektedir. Szasz ve_x000D_ Hollender (1956) üç tür hasta-hekim ilişkisi tanımlamışlardır. Etkinlik-edilgenlik temeline dayanan ilişkide hekim hastanın_x000D_ onamından bağımsız olarak, geniş yetkilerle donanmıştır. Yol gösterme-iş birliği etme temeline dayanan ilişki hekimin_x000D_ komutlarını harfiyen uygulamaya hazır hasta ile hastanın karşısında mesleki deneyimini sunan hekim arasındaki ilişkiyi_x000D_ tanımlar. Karşılıklı katılım temeline dayanan ilişki hekimin, bireyin kendi sağlığına katkı sunması için profesyonel destek_x000D_ sağladığı hasta-hekim ilişkisidir. Hasta-hekim ilişkisi Emanuel EJ ve Emanuel LL (1992) tarafından dört bileşenli bir sınıflama_x000D_ ile modellenmiştir. Paternalistik modelde otoriter tutumu benimseyen hekim hastasının tercihlerini görmezden gelebilir._x000D_ Bilgilendirici modelde durumla ilgili tüm bilgiler hastaya sunulur, hasta kendi seçimini yapar ve doktor seçilen tıbbi_x000D_ müdahaleyi uygular. Yorumlayıcı modelde hekim, hastanın beklentisini ortaya çıkarır, bunu yaparken hastanın değerlerini_x000D_ referans alır ve tedaviyi bu temelde şekillendirir. Hekim ve hasta arasında ortak karar vermeyi teşvik eden uzlaşmacı modelde_x000D_ hekim ve hasta, hastanın tedavi sürecinde ne tür seçenekleri tercih edebileceği ve nihai olarak izlenecek yol konusunda karşılıklı_x000D_ tartışırlar. Unutulmamalıdır ki, klinik görüşmede hangi ilişki türünün benimseneceği hastanın durumuna ve hastalığın_x000D_ özelliğine göre değişebilecektir.
Hasta-Hekim İlişkisine Kavramsal Yaklaşım